Innovative Marketing Trends as a Response to the Changing Consumers - Keskin, Kaan (2013)
In recent years, innovation and the subsequent technological advancements have gained significance in shaping consumer behavior to a disruptive extent. Especially with the advancements in mobile technology, consumer behaviors shifted towards an elevated expectation of mobility and increased interactivity. Marketers who seek a better degree of access to the consumer market and provide customer satisfaction needed to adopt new tools and methods in communication, which would align with their target groups more effectively. Mobile marketing emerged as an innovative technique that is based on and driven by this change in consumer behavior; therefore it is necessary to evaluate the effectiveness of its approach and implementation. In this light, this research paper employs a quantitative approach based on the results' analysis of an online survey conducted by the Author of the thesis, aimed at testing whether there is a strong correlation between mobile marketing efforts and customer satisfaction. Consequently, one can conclude that the same mobile devices that serve as convenience for consumers, serve as an effective channel of communication for marketers, whereas with an integrated approach where other components of the marketing mix support mobile content, the likeliness of attaining consumer satisfaction is higher.